The Federal Constitution and the Choice of Law - Elmer E. Hilpert; Thomas M. Cooley II (Washington University Law Quarterly, 1939)
To what extent may the Constitution of the United States serve as final referent for the problem: "Which state law shall govern cases in which the facts in controversy concern more than one state?" This question has already evoked analyses primarily as a question concerning the conflict of laws ; and in those analyses will be found able and extensive delineation of the general aspect of its problems which will not be repeated here. A simple statement will serve to distinguish the viewpoint adopted in the present discussion. Constitutional law arises solely from express dictates of a written document. It follows that any such question as, "Has the Conflict of Laws become a branch of Constitutional Law?" poses a false problem if taken literally. In the case stated at the opening of this discussion, the Supreme Court could not say, "We find that the conflict of laws rule makes New York's statute the properly governing law, and therefore Georgia's failure to apply it violates the full faith and credit clause. '" The Constitution must furnish the tests for ascertaining the properly applicable law as well as the requirement that it be applied when ascertained. Thus the question may correctly be put: to what extent do the constitutional rules governing choice of law supersede or overlap the conflict of laws rules on the same subject, and what are they?
Keywords: Conflict of laws; Constitutional interpretation -- United States